Improving Student Learning Outcomes Through the Snowball Throwing Model in Learning Public Relations Administration and Protocol at SMK Negeri 1 Barru - Hariani Hariani (Pinisi Journal of Education and Management, 2023)
Snowball is a snowball while Throwing means throwing. Overall, Snowball Throwing can be interpreted as throwing snowballs. Snowball Throwing is formed in groups represented by the group leader to get assignments from the teacher, then each student makes a question shaped like a ball (question paper) and then throws it to other students, each student answers the question from the ball they get. So the aim of this research is to determine whether the Snowball Throwing model can improve student learning outcomes in learning Public Relations and Protocol Administration for Class XII OTKP 3 SMK Negeri 1 Barru for the 2022/2023 academic year. The research method used is classroom action research. The research subjects were 33 students of class XII OTKP 3 SMK Negeri 1 Barru, consisting of 5 boys and 28 girls. The research procedures carried out are based on each cycle, namely planning, implementation, observation, and reflection. Types of data and data collection techniques use qualitative and quantitative data, where qualitative data is collected through observation and documentation. Meanwhile, quantitative data is collected through tests at the end of each cycle. Meanwhile, data analysis techniques use data reduction techniques, data presentation, and drawing conclusions. Data analysis techniques, namely qualitative and quantitative data analysis. The results of the research show that the snowball-throwing model can improve student learning outcomes in Public Relations and Protocol Administration learning for Class. In cycle I, learning management generally went well, but time management still needed to be improved. However, in cycle II learning management improved, and this had a positive impact on student learning completion